Avaliação do efeito do extrato aquoso de Ilex paraguariensis e cafeína sobre o metabolismo e a doença de Alzheimer em Caenorhabditis elegans - Machado, Marina Lopes (2020)
Ilex paraguariensis is a plant widely consumed in South America, used to prepare a tea-like beverage, called mate, rich in caffeine and polyphenols, with multiple biological activities including antioxidant, anti-obesity and neuroprotective proprieties. Nevertheless, studies about the Ilex paraguariensis biological properties are restricted, and its effects over the central nervous system are not well elucidated. Caffeine is a thermogenic agent that acts through the adenosine receptor, and its consumption is associated with a lower risk of age-associated neuropathologies. Alzheimer's disease is a progressive neurodegenerative disorder characterized by the presence of amyloid plaques in the brain formed by the deposition of insoluble β-amyloid peptides. Since several plants that have antioxidant proprieties are known to be neuroprotective, and also caffeine have thermogenic and neuroprotective proprieties, and oxidative stress correlates with Aβ-toxicity, the present study aims to investigate the effects of chronic treatment with Ilex paraguariensis extract in vivo on lipid metabolism and Aβ-induced toxicity model, and compare the effects of this last one with caffeine using Caenorhabditis elegans. Ilex paraguariensis-dependent modulation of fat metabolism in C. elegans was first investigated. Overall, Ilex paraguariensis decreased fat storage and increased body energy expenditure of worms. These effects depend on the purinergic system (ADOR-1) and nuclear hormone receptor (NHR-49), a key regulator gene of fat oxidation. Ilex paraguariensis also upregulated the expression of adipocyte triglyceride lipase 1 (ATGL-1), to modulate fat metabolism. After, the neuroprotective effects of Ilex paraguariensis and caffeine were analyzed. Ilex paraguariensis and caffeine increased the C. elegans lifespan and appeared to act directly as a reactive oxygen species scavenger, also delayed Aβ-induced paralysis and decreased AChE activity in C. elegans. The protective effect of Ilex paraguariensis against Aβ-induced paralysis was found to be dependent on heat shock factor (HSF-1) and FOXO-family transcription factor (DAF-16), which are respectively involved in aging-related processes and chaperone synthesis – responsible for the protein homeostasis; while that of caffeine was dependent only on DAF-16. The results were overall better when C. elegans was treated with Ilex paraguariensis than with caffeine. Due to a large number of constituents in the Ilex paraguariensis extract, it is difficult to identify the precise compound responsible for the beneficial effects. Synergistic interactions are important in phytomedicines, therefore the effects of Ilex paraguariensis extract can be less when a single compound is isolated and used at low concentrations, as in the case of caffeine.